BREEDING DATA PROCESSING APPLICATION IN THE DEPARTMENT NURSERY PT. SELARAS INTI SEMESTA WEB-BASED - Chotimah, Chusnul; Patawaran, Nilfred (MUSTEK ANIM HA, 2024)
Nursery data processing at PT. Aligning with the Core of the Universe is still carried out using Microsoft Excel to input data. The research was conducted to determine the problems in processing data effectively in the use of information system applications and their influence on the quality of data processing, in this case processing nursery data. The research focused on the nursery department, which began by conducting observations, interviews and literature studies. Based on the conditions seen, system development is carried out according to the stages in software engineering, including analysis of system requirements. System design using flowcharts, context diagrams, data flow diagrams (DFD), databases, user interfaces. System implementation uses PHP, MySQL and system testing is carried out using blackbox and user satisfaction testing (UAT). The results of the research are in the form of a Nursery Data Processing Application in the Nursery Department of PT. Web-based Alignment Inti Semesta can help companies process nursery data and obtain nursery data reports. From the questionnaire given to respondents to test the use of the system which is calculated based on entities, results were obtained from respondents admins of 90.3%, from employees 82% and from leaders 90.46%, so that the system developed was very helpful to the company.